Report on the Excavations at the Roman Fort of Cappuck, Roxburghshire - Stevenson, G H; Miller, S N (Proceedings of the Society of Antiquaries of Scotland, 1912)
The fort is located on the line of Dere Street. The internal measurement from north to south was 80 yards, and from east to west 70 yards. This gives an area of about one and a quarter acres, while an almost equal space is covered by the defences. Cappuck is thus considerably smaller than most of the Roman forts hitherto excavated in Britain. A great deal of plough damage has occurred. The whole fort had been surrounded by a clay rampart, resting in part on a layer of cobble-stones, although the defences on the east side seem to have been more complex. Cappuck is distinguished from the other Roman forts in Scotland by the possession of only one gate. The buildings of the interior are described and a detailed report on the artefacts is presented. The datable objects found on the site show that the fort was Agricolan in origin.